Analisis Faktor-Faktor yang Mempengaruhi Kepatuhan Wajib Pajak Membayar Pajak Bumi dan Bangunan Kota Batam - Windy Safitri; Anggun Permata Husda (SEIKO : Journal of Management & Business, 2022)
Abstrak This study aims to determine the factors that influence taxpayer compliance in paying land and building taxes in Batam City. Research is quantitative. The population in this study are people who live in Bota Batam, Sekupang District, who are registered as PBB taxpayers with sampling using Slovin getting 400 respondents. The Likert scale used. The results of this study use SPSS form 25. The awareness variable which is confirmed by the t-count value of 14.821 has exceeded 1.971 which is the t-table value at probability 0.05 and the significance value for the awareness variable is 0.000 and does not exceed 0.05. significant to compliance. The knowledge variable which is confirmed by the calculated t value of 4.991 has exceeded 1.971 which is the t table value at probability 0.05 and the significance value for the knowledge variable is 0.000 and does not reach 0.05. knowledge variable has a significant effect on compliance. The sanctions variable which is confirmed by the t-count value of 1.981 has exceeded 1.988 which is the t-table value at probability 0.05 and the significance value for the sanctions variable is 0.005 and does not reach 0.05, the sanctions variable has a significant effect on compliance. Simultaneously give effect to the dependent variable. In other words, the variables of awareness, knowledge and sanctions have a simultaneously significant effect on the compliance variable Keyword : taxpayer compliance, paying land and building taxes, Batam City